Self-Healing Behaviour of Pre-Cracked POFA-Concretes Under Curing Conditions - Khairul Anuar, Shahid; Mohd Faizal, Md Jaafar; Norhaiza, Ghazali; Fadzil, Mat Yahaya (2013)
The investigation on the effect of curing conditions to self-healing of pre-cracked concrete containing palm oil fuel ash (POFA-concrete) are presented. POFA cement was replaced from 10%, 20% and 30% from the total weight of ordinary Portland cement (OPC). Four (4) types of curing condition namely air, room temperature,wet and dry, and water curing were carried out. The ultra-pulse velocity(UPV) test was performed to monitor the self-healing progress on POFA-concrete. The result shows 20% POFA-concrete recorded highest compressive strength compare to those mixes. It is also revealed the UPV readings were increased significantly with the increase curing ages. The results also obtained the self-healing ability of precracked POFA-concrete at 10% replacement level increase significantly for water curing condition.